Регистрация
Войти
Стать экспертом Правила
Алгебра

посчитайте решить этот пример

ОТВЕТЫ

 \lim_{x \to 1} \frac{(2 + x) {}^{3} - (4 - x) {}^{3}}{(1 + x) {}^{3}- (3 - x) {}^{3} }=\lim_{x \to 1} \frac{(2 + x - 4 + x)((2 + x) {}^{2} + (2 + x)(4 - x) + (4 - x) {}^{2})}{(1 + x- 3 + x)((1 + x) {}^{2}+ (1 + x)(3 - x) + (3 - x) {}^{2} }=\lim_{x \to 1} \frac{(2x - 2)(4 + 4x +{x}^{2} + 8+ 2x -{x}^{2}+ 16 - 8x +{x}^{2} )}{(2x - 2)(1 + 2x +{x}^{2} + 3 + 2x -{x}^{2} + 9 - 6x +{x}^{2})}=\lim_{x \to 1} \frac{28 - 2x +{x}^{2} }{13 - 2x +{x}^{2} }=\frac{28 - 2+ 1}{13 - 2 + 1}=\frac{27}{12}=\frac{9}{4}= 2.25

: 2.25

82
Контакты
Реклама на сайте
Спрошу
О проекте
Новым пользователям
Новым экспертам